2019
DOI: 10.2320/matertrans.m2019057
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Dendrite Coarsening and Microsegregation in Al–Cu Alloy under a Steady Magnetic Field

Abstract: The final mechanical properties of alloys are significantly influenced by the secondary dendrite arm spacing (SDAS). The application of a steady magnetic field (SMF) during solidification is a novel method to control the SDAS, however, the nature of the change in SDAS under an SMF is still an open question. In this work, dendrite coarsening in the Al4.5 mass%Cu alloy in an SMF and its effect on microsegregation were investigated experimentally by the quenching technique. The coarsening experiments showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…He et al investigated dendrite coarsening in the Al 4.5 wt% Cu alloy in the SMF by the quenching technique [17]. The experimental results showed that the SDAS increased in the SMF (Figure 7), which is attributed to the TEM convection as well as the change in solid/liquid interfacial tension.…”
Section: Dendrite Coarsening In Smfmentioning
confidence: 99%
See 1 more Smart Citation
“…He et al investigated dendrite coarsening in the Al 4.5 wt% Cu alloy in the SMF by the quenching technique [17]. The experimental results showed that the SDAS increased in the SMF (Figure 7), which is attributed to the TEM convection as well as the change in solid/liquid interfacial tension.…”
Section: Dendrite Coarsening In Smfmentioning
confidence: 99%
“…In this review, we emphasize the state of the art of solidification processing in the static magnetic field (SMF). The numerous studies confirm that applying the SMF to metal solidification processes is a promising and novel strategy to modify nucleation [14], undercooling [15], interface free energy [16], grain coarsening [17] and refinement [18], segregation [19], and porosity [20]. Although the magnetic field has exerted significant effects on metal solidification processes, its applicability needs further development and the related physical mechanisms deserve further elucidation.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, magnetic dipole-dipole interactions (or magnetic interaction force) have been successfully used to affect grain growth, resulting in elongated grain and chainlike microstructures [40], and control the agglomeration and dispersion of primary crystals [51]. Therefore, the aforementioned forces, which have significant effects on the kinetic processes of solidification, are effective in controlling atom diffusion [52][53][54][55][56], nucleation events [42,57], melt convection [19,34], solute distribution [32,58,59], crystal migration [21,43,60], and morphology evolution [61][62][63] during solidification. Apart from kinetic processes, magnetic energy can also modify thermodynamic events, such as phase transformation and crystal orientation, even in a non-ferromagnetic system [12,64,65].…”
Section: Introductionmentioning
confidence: 99%